Analisis Pengaruh Iklim Kerja Dan Pengembangan Karir Terhadap Komitmen Karir Dengan Kepuasan Kerja Sebagai Variabel Intervening - Salindeho, Charles L (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
The result of the research show that work climate and career development has influence significantly to good joob satisfaction in parsial as well as in simultionously to the staff of the regional secretariat of Siau Tagulandang Bintaro archipelago regency. Work climate and career development has influence significantly to career commitment in parsial as well as insimultionously to the staff of the regional secretariat of Siau Tagulandang Bintaro archipelago regency. Job satisfaction has influence to career comitment to the staff.Keywords: Climate work, career development, job satisfaction, career commitment